Efektivitas Aplikasi Quizizz terhadap Kemampuan Metakognisi Mahasiswa UPBJJ UT-Majene pada Mata Kuliah Pendidikan Kewarganegaraan - Abdul Latif (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2021)
21st century learning in the classroom is characterized by the use of ICT, collaboration, communication, and critical and creative thinking. To optimize the learning, it is necessary to optimize the metacognitive ability of students. This research is a quasi-experimental study by treating the application of the quizizz application to UPBJJ UT-Majene students, majoring in PGSD who programmed citizenship education courses. The research resulted in learning tools, namely Quizizz and RAT-SAT. The data collection tools used are performance tests, observation sheets, and student response questionnaires to the application of quizzz on metacognitive abilities. The data analysis used is descriptive statistical analysis and inferential statistics. The results showed that the quizizz application was effective on the metacognitive abilities of UPBJJ UT-Majene students, majoring in PGSD in civic education courses.